PERTARUNGAN HUKUM SHARI’AH DAN KAPITALISME DALAM SISTEM PERBANKAN KONTEMPORER DI INDONESIA - Muhammad Hasan (Al-Maslahah : Jurnal Ilmu Syariah, 2016)
Islamic banking is a bank that operates based on economic principles that set in Islamic law. The capitalist system with its interest concept is an economic system that has some variants contrary to Islamic law. Although, the concept of interest a debate among Muslim scholars and scientists, but the presence of Shari’ah banking has proven economic expert support Muslims with the prohibition of interest system. Philosophically and axiology profit and loss sharing, sale and purchase, and the system of interest has its implications. Rate system is a system that is contrary to shari'ah banking operating system, but often the existing product ownership in the shari'ah as the product mura>bah}ah is identical to the system of interest. Similarly, other products are still difficult to distinguish from conventional systems / capitalist in its operations. On the plains, epistemology, banking products shari'ah should be improved so that it becomes a pure economic system is based on Islamic law, not the capitalist system of legalized with the philosophy of Islamic law. In other words, there needs to be alignment between the philosophical and epistemological aspects in the development of banking products shari'ah. Keywords: Profit sharing, murãbahah, islamic law, riba’, bank, interets.